ALGODYSTROPHY, SYMPATHECTOMY AND REGIONAL PAIN SYNDROME: A CASE REPORT AND REVIEW OF THE LITERATURE - Ayhan Kamanlı; Arzu Kaya; Sezai Şahin; Vural Kavuncu; Özge Ardıçoğlu (Archives of Rheumatology, 2001)
Algodystrophy is an important pain syndrome characterized by variable dysfunction of musculoskeletal, skin and vascular systems, resulted from authonomic dysregulation. In this article, a 28 year-old female patient with reflex sympathetic dystrophy syndrome underwent sympathectomy has been reported, algodystrophy and its synonyms have been discussed under the light of current literature.